Cultural and Socioeconomic Influences on Medicine Choice: A Comparative Review of Herbal and Pharmaceutical Drug Preferences - Yani, Ahmad (Jurnal Riset Kualitatif dan Promosi Kesehatan, 2024)
Occupational stress among healthcare workers has become an urgent global concern, exacerbated by increased workloads, insufficient institutional support, and poor working conditions. This study aims to examine the primary stressors affecting medical professionals and evaluate existing interventions. A systematic review of peer reviewed literature from PubMed, Scopus, Google Scholar, and Cochrane Library was conducted, focusing on studies published between 2019 and 2024. Inclusion criteria encompassed empirical research on healthcare worker stress, while non English, non peer reviewed, and non empirical studies were excluded. The findings indicate that excessive workload, lack of workplace support, and emotional distress are major contributors to stress. High intensity settings such as intensive care units (ICUs) exhibit greater stress levels than primary care facilities. Healthcare workers in low resource environments experience disproportionately higher stress due to limited infrastructure and inadequate psychological support. Effective coping mechanisms include peer support, humor, and institutional interventions such as Employee Assistance Programs (EAPs). Digital mental health solutions and policy driven interventions have proven beneficial in reducing occupational stress. The study concludes that structured institutional support, mental health training, and flexible work policies are essential in mitigating stress among healthcare professionals. Further research should explore long term stress impacts and evaluate innovative interventions to improve workforce resilience and patient care quality.